Cholecystoduodenal fistula presenting with refractory upper gastrointestinal bleeding: retrospective analysis: a case report - Zhen Zhao; Zihao Fan; Tianpeng Zhang (Journal of Medical Case Reports)
Abstract Background Spontaneous cholecystoduodenal fistula presents an uncommon complication arising from cholelithiasis. Its symptoms are typically nonspecific and can closely mimic those of other chronic biliary diseases, therefore increasing the likelihood of misdiagnosis. Massive upper gastrointestinal bleeding complicated with cholecystoduodenal fistula is an extremely rare condition with only a few documented cases. Case presentation Here we discuss the case of a 77-year-old Han Chinese female who presented with refractory upper gastrointestinal bleeding due to a cholecystoduodenal fistula. The patient was diagnosed through a comprehensive analysis of using computed tomography, esophagogastroduodenoscopy, contrast‑enhanced ultrasound, and endoscopic retrograde cholangiopancreatography. Additionally, we present a literature review and retrospective study to provide further context and insights into this rare condition. Given the rarity and diagnostic challenges of cholecystoduodenal fistula presenting primarily with upper gastrointestinal bleeding, we conducted a retrospective analysis of cases diagnosed at our institution over the past two decades. Only four cases (including the current one) manifested with gastrointestinal hemorrhage as the initial symptom. Conclusions Acute upper gastrointestinal bleeding caused by cholecystoduodenal fistula is very challenging to diagnose. Physicians involved in the management of patients with upper gastrointestinal bleeding should consider the possibility of a biliary-enteric fistula as a possible cause, especially in patients with risk factors for gallstone disease. Contrast‑enhanced ultrasound may facilitate prompt diagnosis in such cases. Strengths and limitations The Beijing Friendship Hospital affiliated with Capital Medical University serves as China’s national-level clinical research center for digestive system diseases. Consequently, there is an ample supply of clinical cases even for the rare cholecystoduodenal fistula. Through summarizing the diagnosis, treatment, and outcome of this disease category, it holds the potential to offer valuable support for the future diagnosis and treatment of cholecystoduodenal fistula. Furthermore, we performed a 20-year institutional retrospective analysis of cholecystoduodenal fistula. This systematic review exemplifies our center’s clinical expertise in managing this rare condition when it manifests as acute upper gastrointestinal bleeding. While our findings provide valuable insights, the limited cohort size (n = 4) necessitates caution in extrapolating these results to broader populations. Multicenter studies with larger samples are warranted to validate our observations.